Measurement of Soluble Arsenic in Soil of Bangladesh by Acid-alkali Sequential Extraction - Azam, Mohammad Shafiul; Shafiquzzaman, Md.; Mishima, Iori; Nakajima, Jun (Journal of Scientific Research, 2008)
To measure easily soluble fraction of arsenic, a sequential extraction method by 0.1N HCl and 0.1N NaOH was used according to the soil phosphorus extraction procedure. The effects of reducing conditions on arsenic extraction were examined in incubation test. In high reducing conditions arsenic solubility was shown to be high and seemed to be controlled by dissolution of iron oxy-hydroxides. pH played a predominant role in determining the concentrations of soluble arsenic. Arsenic solubility could be possible at low or high pH conditions. Released arsenic in different pH and redox conditions showed that it is a part of acid extractable arsenic which is sorbed weakly on the soil surface and can be extracted during acid-alkali sequential extraction. Therefore, the method could be applicable to measure potential solubility of arsenic as a result of alteration in soil (e.g. redox, pH) and environmental factors. Sequential extraction results of the soil samples collected in dry and wet season suggested that acid-alkali extracted arsenic fractions of surface and core soil samples of paddy field were increased in wet season. They seemed to be moved with irrigation groundwater. Â Keywords: Acid-alkali extraction; Arsenic contamination; Soil arsenic mobility; Groundwater contamination; Paddy soil. Â Â© 2009 JSR Publications. ISSN: 2070-0237(Print); 2070-0245 (Online). All rights reserved. Â DOI: 10.3329/jsr.v1i1.1058 Â Â